The Value of Human Dignity - Ezenwa, Paul Chinedu (My University, 2017)
Starting from conception till death, man as a being relates with others. In this relationship he often encounters lots of problems that threaten his existence. One of them is the threat to his dignity. This experience is vivid in many countries particularly in Africa. But my work is limited to an ethnic group in Nigeria, namely Igbo people. The work discloses the extent 'displacement of value' in Igboland has contributed to the devaluation of human dignity and the attempts made to combat it. This displacement resulted in what we can call "value crisis". Some elements, like Igbo culture and cultural communication with foreign cultures that have tentacles in modernized orientation, are discussed as 'transmission carriers'. In order to x-ray properly the heart of this research and communicate the necessary messages, the work is presented in six chapters. However, this summary will not be presented in chapters. Thus the need for a research on the reason for the failings and crisis of approach regarding this aspect of Igbo life that deals with the value of human dignity. This comes to term with the question which asked has the interest in the enhancement of the dignity of man waned because the effort towards this goal seem futile and unnecessary…Or is human dignity something we care about but take for granted as a cultural inheritance that no longer needs defence?” This question arouses thoughts on the value of HD. The entire work tried to justify the view that the protection of HD is for all times a true assignment of all. This must neither be considered to be relevant only for a time nor only for a portion or a group of individuals. Thus a special attention on this regard is demanded especially in modern day Igbo society.
A Socio-Cultural Approach to Analyzing the Crisis of Values among Igbo People of Nigeria
Keywords: Kultur; Gesellschaft; Geschlechterdifferenz; Ethik; Religion; Wandel; 170 Ethik; Würde; Nigeria; Igbo